Geotechnical frontiers 2017. selected papers from sessions of Geotechnical Frontiers 2017, March 12-15, 2017, Orlando, Florida - Brandon, Thomas L.; Valentine, Richard, J. (American Society of Civil Engineers, 2017)
Contains 39 peer-reviewed papers on various foundation types. Topics include: bridge and offshore structures, scour, geosynthetics in foundations, offshore foundation systems, and pile, shaft and pier foundations.
Keywords: Geotechnical engineering -- Congresses.; Foundations -- Design and construction -- Congresses.; Offshore structures -- Foundations -- Congresses.; Bridges -- Foundations and piers -- Congresses.; Scour and fill (Geomorphology) -- Congresses.; Soil mechanics -- Congresses.; Piling (Civil engineering) -- Congresses.; elektronické knihy; electronic books